xy + xz = -1
xy + yz = -9
yz + xz = -4
solve for (x,y,z)
I'd suggest substituting xy = a, xz = b and yz = c. Solve the three new linear equations simultaneously for a, b and c. NOw use these values to solve for x, y and z.
By the way ..... There are several good reasons NOT delete questions once they've been answered. (I refer to your edit at http://www.mathhelpforum.com/math-he...-question.html)
Hello Stasis. This problem can easily be solved by doing some basic elimination and substitution.
My approach starts with (1) - (2) to give call this (4)
then (3) + (4) give
substitute into (1) and (3) to get and
so we have:
now (7)*(5) gives (6) gives therefore
putting in (5) gives
and into (7)
so your two solutions are
Bobak